2021
DOI: 10.4149/gpb_2021008
|View full text |Cite
|
Sign up to set email alerts
|

Identification of an autophagy-related 10-lncRNA-mRNA signature for distinguishing glioblastoma multiforme from lower‑grade glioma and prognosis prediction

Abstract: Autophagy may provide the source of nutrients for tumor cells. We aim to develop an autophagy-related signature to predict the progression from lower-grade gliomas (LGG) to glioblastoma multiforme (GBM) and prognosis. Totally, 686 differentially expressed genes (DEGs) and 73 long non-coding RNAs (DELs) were identified between GBM and LGG samples from the Chinese Glioma Genome Atlas (CGGA). Of them, 131 DEGs were intersected with autophagy genes from the Human Autophagy Database; while 54 DELs co-expressed with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 58 publications
0
4
0
Order By: Relevance
“…Using univariate and multivariate Cox analyses, we found that older age and m6A risk score were independent risk factors for predicting the prognosis of patients with glioma. A previous study found that age was an independent risk factor for GBM, and aging resulted in a poorer prognosis ( Wei et al, 2020 ). Our results are consistent with those of previous studies.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Using univariate and multivariate Cox analyses, we found that older age and m6A risk score were independent risk factors for predicting the prognosis of patients with glioma. A previous study found that age was an independent risk factor for GBM, and aging resulted in a poorer prognosis ( Wei et al, 2020 ). Our results are consistent with those of previous studies.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, the prognosis of individual patients with glioma is difficult to predict because few clinical biomarkers or parameters are available to reflect disease progression and neurological outcomes. Although a series of functional gene sets have been identified, the exact roles of these clusters remain to be elucidated ( He et al, 2020 ; Wei et al, 2020 ; Zhang et al, 2021 ). Thus, a better understanding of the molecular mechanisms of glioma, including its genetic background and prognosis-related factors, is essential for the diagnosis and treatment of this malignant disease.…”
Section: Introductionmentioning
confidence: 99%
“…The signature could distinguish GBM from LGG and predict OS in glioma patients, which also validated using TCGA dataset. 48 Five-ATG signature identified by Guo et al using two datasets was validated that it had good predictive performance. 49 Xu et al used 15ARGs to construct a risk model that could predict the prognosis of glioma patients.…”
Section: Discussionmentioning
confidence: 94%
“…10 Long non-coding RNA (lncRNA) is an RNA molecule composed of more than 200 nucleotides, 11 which is closely related to the occurrence and development of tumors and can be used as a potential marker for tumor diagnosis and prognosis. 12 At the same time, a large amount of evidence shows that lncRNA is an active participant in all stages of tumor immunity. 13 In recent years, with the continuous development of gene sequencing technology, bioinformatics databases have been widely used in the field of medical research.…”
Section: Introductionmentioning
confidence: 99%